ANALISIS KAUSALITAS CURRENT ACCOUNT DEFICIT DENGAN KETERBUKAAN PERDAGANGAN,NILAI TUKAR RIIL EFEKTIF, FOREIGN DIRECT INVESMENT, DAN PERTUMBUHAN EKONOMI INDONESIA - Sekar Lunggayu Kartika; Dewi Zaini Putri; Hasdi Aimon (Universitas Negeri Padang, 2019)
This study aims to reveal and analisys the causality between the macro aggregates that affect currenct account deficit using Granger causality test. Current account deficit/GDP, trade openness, real effective exchange rate, growth rate, and foreign direct investment were selected as variabels for this research.The research methods used are: (1) Stationarity Test; (2) Optimal Lag Lenght; (3) Cointegration Test (based on the results of the cointegration test obtained, this study must be continued using the VECM method); (4) Granger Causality Test; (5) Estimation of the VECM Model (6) Impulse Response Function; (7) Variance Decomposition.The result of the Granger causality test demonstrate that: (1) There is no causal relationship between the current account deficit and trade openness in Indonesia; (2) There is no causal relationship between the current account deficit and real effective exchange rate in Indonesia (3) There is a causal relationship between the current account deficit and economic growth in Indonesia; (4) There is no causal relationship between the current account deficit and foreign direct investment in Indonesia.